2004
DOI: 10.1111/j.1600-6143.2004.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles of Polyethylene Glycol and Trimetazidine against Cold Ischemia and Reperfusion Injuries of Pig Kidney Graft

Abstract: Ischemia-reperfusion injury (IRI) represents an alloindependent risk factor which favors chronic allograft nephropathy (CAN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Myeloid and lymphoid cell numbers increased both in the subglottis and trachea (data not shown for the trachea) while decreases were observed in the supraglottis. In other systems, increases in cell numbers are associated with histological and/or functional injury [27,28], suggesting that the supraglottis may have been less affected by the insults applied here. However, this does not explain the observation that cell numbers actually decreased in the supraglottis, suggesting active mobilization from the site.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid and lymphoid cell numbers increased both in the subglottis and trachea (data not shown for the trachea) while decreases were observed in the supraglottis. In other systems, increases in cell numbers are associated with histological and/or functional injury [27,28], suggesting that the supraglottis may have been less affected by the insults applied here. However, this does not explain the observation that cell numbers actually decreased in the supraglottis, suggesting active mobilization from the site.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the antioxidant role of TMZ in the renal I/R injury has been investigated by administering it in vivo or by adding it to preservation solutions used for kidney transplantation [5,[10][11][12] . In addition, it has been suggested that TMZ can prevent the injury of the kidney as a remote organ by diminishing systemic oxidative stress in the body in the situations of I/R elsewhere [13] .…”
Section: Effectiveness Of Trimetazidine In Testicular Torsionmentioning
confidence: 99%
“…Moreover, the vascular endothelium is also a key site of injury from ROS and endothelial cell dysfunction is central to the pathogenesis of chronic allograft nephropathy (2,3). We have previously evidenced the protective effect of TMZ on kidney grafts from cold preservation and reperfusion, showing that TMZ was efficient when added to various currently used preservation solutions (11,12). Several reports have described different pharmacological effects of TMZ which are relevant in the prevention of organ damage from IRI: partial inhibition of fatty acid ␤-oxidation (20), reduction of ionic imbalance during ischemia-reperfusion (I/R) (9), increase in phospholipid uptake turnover (33), and membrane protection against reoxygenation-induced stress (32,28).…”
mentioning
confidence: 99%